Comparison of the efficacy and safety of 0.1% tacrolimus ointment and 0.1% mometasone furoate cream for adult vitiligo: A single-blinded pilot study - Narumol Silpa-Archa; Sunatra Nitayavardhana; Kanchalit Thanomkitti; Leena Chularojanamontri; Supenya Varothai; Chanisada Wongpraparut (Wolters Kluwer Medknow Publications, 2016)
Topical tacrolimus has demonstrated efficacy in vitiligo. This study compared the efficacy and safety of 0.1% tacrolimus ointment with 0.1% mometasone furoate cream in adult vitiligo. We enrolled patients with symmetrical, nonacral vitiligo, and the patients on each side were randomized to receive either 0.1% tacrolimus ointment or 0.1% mometasone furoate cream, applied twice daily for 6 months. Repigmentation outcome at 6 months was compared with baseline. Of 18 cases, 22% and 33% in tacrolimus and mometasone groups, respectively, displayed more than 50% repigmentation (p > 0.05). Telangiectasia was presented in one-third of cases on the mometasone-treated side. Both treatments were effective in vitiligo; however, 0.1% tacrolimus ointment has fewer adverse effects.